Associations between Gene-Gene Interaction and Overweight/Obesity of 12-Month-Old Chinese Infants. (7th March 2022) - Mei, Hong; Yin, Baoming; Yang, Wenhong; Zhang, Jingli; Lu, Hongyan; Qi, Xiaobin; Mei, Wenhua; Zhang, Hongzhong; Zhang, Jianduan
Abstract : Background . Childhood overweight and obesity (OW/OB) is a worldwide public health problem, and its genetic risks remain unclear. Objectives . To investigate risks of OW/OB associated with genetic variances in SEC16B rs543874 and rs10913469, BDNF rs11030104 and rs6265, NT5C2 rs11191580, PTBP2 rs11165675, ADCY9 rs2531995, FAM120A rs7869969, KCNQ1 rs2237892, and C4orf33 rs2968990 in Chinese infants at 12-month old. Methods . We conducted a case-control study with 734 infants included at delivery and followed up to 12-month old. The classification and regression tree analysis were used to generate the structure of the gene-gene interactions, while the unconditional multivariate logistic regression models were applied to analyze the single SNP, gene-gene interactions, and cumulative effects of the genotypes on OW/OB, adjusted for potential confounders. Results . There were 219 (29.84%) OW/OB infants. Rs543874 G allele and rs11030104 AA genotype increased the risk of OW/OB in 12-month-old infants (P < 0.05 ). Those carrying both rs11030104 AA genotype and rs10913469 C allele had 4.3 times greater OW/OB than those carrying rs11030104 G allele, rs11191580 C allele, rs11165675 A allele, and rs543874 AA genotype. Meanwhile, the risk of OW/OB increased with the number of the risk genotypes individuals harbored. Conclusions . Rs543874, rs11030104, and rs11191580 were associated with OW/OB in 12-month-old Chinese infants, and the three SNPs together with rs10913469 and rs11165675 had a combined effect on OW/OB.